Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Select the correct answer.

For which system of inequalities is [tex]$(3,-7)$[/tex] a solution?

A.
[tex]\[
\begin{array}{l}
x + y \ \textless \ -4 \\
3x + 2y \ \textless \ -5
\end{array}
\][/tex]

B.
[tex]\[
\begin{array}{l}
x + y \leq -4 \\
3x + 2y \ \textless \ -5
\end{array}
\][/tex]

C.
[tex]\[
\begin{array}{l}
x + y \ \textless \ -4 \\
3x + 2y \leq -5
\end{array}
\][/tex]

D.
[tex]\[
\begin{array}{l}
x + y \leq -4 \\
3x + 2y \leq -5
\end{array}
\][/tex]


Sagot :

To determine which system of inequalities [tex]\((3, -7)\)[/tex] is a solution for, we will evaluate each system step-by-step.

### System A:
1. [tex]\(x + y < -4\)[/tex]
- Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = -7\)[/tex]
- [tex]\(3 + (-7) = -4\)[/tex]
- Check: [tex]\(-4 < -4\)[/tex] (False)

2. [tex]\(3x + 2y < -5\)[/tex]
- Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = -7\)[/tex]
- [tex]\(3(3) + 2(-7) = 9 - 14 = -5\)[/tex]
- Check: [tex]\(-5 < -5\)[/tex] (False)

Both inequalities must be true for the system to be true. Since the first condition is false, [tex]\( (3, -7) \)[/tex] does not satisfy system A.

### System B:
1. [tex]\(x + y \leq -4\)[/tex]
- Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = -7\)[/tex]
- [tex]\(3 + (-7) = -4\)[/tex]
- Check: [tex]\(-4 \leq -4\)[/tex] (True)

2. [tex]\(3x + 2y < -5\)[/tex]
- Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = -7\)[/tex]
- [tex]\(3(3) + 2(-7) = 9 - 14 = -5\)[/tex]
- Check: [tex]\(-5 < -5\)[/tex] (False)

Both inequalities must be true for the system to be true. Since the second condition is false, [tex]\( (3, -7) \)[/tex] does not satisfy system B.

### System C:
1. [tex]\(x + y < -4\)[/tex]
- Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = -7\)[/tex]
- [tex]\(3 + (-7) = -4\)[/tex]
- Check: [tex]\(-4 < -4\)[/tex] (False)

2. [tex]\(3x + 2y \leq -5\)[/tex]
- Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = -7\)[/tex]
- [tex]\(3(3) + 2(-7) = 9 - 14 = -5\)[/tex]
- Check: [tex]\(-5 \leq -5\)[/tex] (True)

Both inequalities must be true for the system to be true. Since the first condition is false, [tex]\( (3, -7) \)[/tex] does not satisfy system C.

### System D:
1. [tex]\(x + y \leq -4\)[/tex]
- Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = -7\)[/tex]
- [tex]\(3 + (-7) = -4\)[/tex]
- Check: [tex]\(-4 \leq -4\)[/tex] (True)

2. [tex]\(3x + 2y \leq -5\)[/tex]
- Substitute [tex]\(x = 3\)[/tex] and [tex]\(y = -7\)[/tex]
- [tex]\(3(3) + 2(-7) = 9 - 14 = -5\)[/tex]
- Check: [tex]\(-5 \leq -5\)[/tex] (True)

Both inequalities are true. Therefore, [tex]\((3, -7)\)[/tex] satisfies system D.

### Conclusion:
The point [tex]\((3, -7)\)[/tex] is a solution to system D.
So, the correct answer is:
D.
[tex]\[ \begin{array}{l} x+y \leq-4 \\ 3 x+2 y \leq-5 \end{array} \][/tex]